2020
DOI: 10.1093/nop/npaa074
|View full text |Cite
|
Sign up to set email alerts
|

Quality of patient-reported outcome reporting according to the CONSORT statement in randomized controlled trials with glioblastoma patients

Abstract: Background Randomized controlled trials (RCTs) represent the best evidence in oncology research. Glioblastoma is the most frequent and deadly primary brain tumor, impacting health-related quality of life. An important endpoint is patient-reported outcomes (PROs). There is no data regarding how well publications of glioblastoma’s RCTs report PROs. A specific PRO extension of the CONSORT statement was created to improve quality of reporting. The aim of this study was to evaluate the adherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…[ 22 ] Despite our study’s finding that The CONSORT OQS remains deficient; it is encouraging that we have already seen increasing uptake of the CONSORT criteria in the neurosurgery literature as a whole. [ 18 , 23 , 24 ] We observed that reporting quality improved over time and the OQS of RCTs was significantly higher when published since 2010 ( P = .012). Tardy et al also noticed an improvement in the CONSORT Score and definition of inclusion criteria over the years, revealing an effort to define more homogeneous groups.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[ 22 ] Despite our study’s finding that The CONSORT OQS remains deficient; it is encouraging that we have already seen increasing uptake of the CONSORT criteria in the neurosurgery literature as a whole. [ 18 , 23 , 24 ] We observed that reporting quality improved over time and the OQS of RCTs was significantly higher when published since 2010 ( P = .012). Tardy et al also noticed an improvement in the CONSORT Score and definition of inclusion criteria over the years, revealing an effort to define more homogeneous groups.…”
Section: Discussionmentioning
confidence: 88%
“…Well-designed and properly executed RCTs provide the most reliable evidence for the efficacy of healthcare interventions; however, trials with inadequate methods are associated with bias, especially exaggerated treatment effects. [23,25] Our study has several limitations. First, improvements in study reporting based on the flaws revealed by the current research may have a disproportionately large effect on the quality of study reporting given the limited number of studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, it is essential to consider quality of life, patient reported outcome, and toxicity before implementing a new treatment in clinical practice. 160 , 162 …”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Since the publication of this guideline in 2013, a number of systematic reviewa have evaluated the quality and completeness of PRO reporting against this standard [14][15][16][17][18]; results of such reviews have shown that up to 50% of included studies show "sub-optimal reporting".…”
Section: Introductionmentioning
confidence: 99%